2014
DOI: 10.1093/eurheartj/ehu304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of right ventricular pacing lead site on left ventricular function in patients with high-grade atrioventricular block: results of the Protect-Pace study

Abstract: ClinicalTrials.gov number NCT00461734.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
188
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(198 citation statements)
references
References 31 publications
3
188
2
5
Order By: Relevance
“…However, true RV septal pacing and His bundle pacing are limited by the difficulty of achieving stable lead positions. 25,26 The most commonly used alternative site is the RV outflow tract, but there is as yet no randomized trial evidence that supports the superiority of this pacing site compared with RV apical pacing. 27 Biventricular pacing is a well-established therapy for HF patients with LV ejection fraction (LVEF) <35% and wide QRS complex duration.…”
Section: Comparison Of Rv and Biventricular Pacing For Avb Patientsmentioning
confidence: 99%
“…However, true RV septal pacing and His bundle pacing are limited by the difficulty of achieving stable lead positions. 25,26 The most commonly used alternative site is the RV outflow tract, but there is as yet no randomized trial evidence that supports the superiority of this pacing site compared with RV apical pacing. 27 Biventricular pacing is a well-established therapy for HF patients with LV ejection fraction (LVEF) <35% and wide QRS complex duration.…”
Section: Comparison Of Rv and Biventricular Pacing For Avb Patientsmentioning
confidence: 99%
“…7 However, 3 randomized trials comparing RVS with RVA pacing in patients with congestive heart failure and chronic atrial fibrillation and patients with total AV block showed no differences in LV ejection fraction, quality of life, exercise capacity, and brain natriuretic peptide levels at longterm follow-up. 8,16,17 Previous acute hemodynamic studies in dogs with normal ventricular conduction have demonstrated that pacing at the LVS maintains LV systolic and diastolic function at sinus rhythm level, whereas LV function is depressed during RVA and RVS pacing. 10,11 The data from this study extrapolate these preclinical findings on the beneficial hemodynamic effect of LVS pacing to the human population.…”
Section: Lvs Pacing Versus Rva and Rvs Pacingmentioning
confidence: 99%
“…Alternative pacing sites within the right ventricle (RV), such as the RV septum (RVS) or RV outflow tract, have been intensively studied but show mixed results. [7][8][9] Studies on animals have shown that pacing at the LV septum (LVS) yields LV pump function closely approximating that during normal ventricular conduction and significantly better than that during RVS pacing. 10,11 In the animal experiments, the LVS lead was permanently placed by introducing a custom pacing lead with extended helix transvenously into the RV and driving it from the RV side through the interventricular septum (IVS) to the LVS.…”
mentioning
confidence: 99%
“…However, a benefit of high septal pacing on preservation of ventricular function or prevention of AF or HF events was not observed in the ProtectPace study, which randomized 240 patients with high-grade AV block to high septal or RV apical pacing. 38 It is now well established that pacing at the RV outflow tract or septal locations can be achieved with acceptable pacing thresholds and minimal risk of complications, including lead dislodgement, and this approach seems to be increasingly adapted into clinical practice. Although promising, pacing from sites in the His bundle region remains problematic with lower success rates, higher pacing thresholds, and longer procedure times.…”
Section: Alternative Rv Pacing Sitesmentioning
confidence: 99%